What are the factors affecting dual-task gait performance in people after stroke?. (4th May 2022) - Muci, Birsen; Keser, Ilke; Meric, Aydin; Karatas, Gulcin Kaymak
ABSTRACT: Background: People after stroke have difficulties when they undertaking two tasks simultaneously. Purposes: To investigate the relationships between dual-task performance and factors such as motor function, balance, cognitive state, and fatigue, to identify factors that have an impact on dual-task performance after a stroke. Methods: Thirty-seven people with stroke and 38 healthy participants were assessed with 10-m walking test in different performances which were single-task-based, motor dual-task-based and cognitive dual-task-based. Results were evaluated according to the Rivermead Motor Assessment, the Static balance index, the Mini-Mental State Examination, and the Fatigue Severity Scale. Results: Participants with stroke were slower compared to the control group with the following mean speed values for single-task (M = 0.73 m/s, t = −7.612, p < .001), motor dual-task (M = 0.70 m/s, t = −8.232, p < .001), cognitive dual-task (M = 0.59 m/s, t = −7.944, p < .001). For people after stroke, motor dual-task performance was significantly affected by the total motor function scores (r = 0.648, p < .001), static balance (r = −0.499, p < .05), and fatigue rates (r = −0.349, p < .05). Furthermore, cognitive dual-task performance was affected by the total motor function score (r = 0.537, p < .05) static balance (r = −0.541, p < .05) and fatigue rates (r = −0.350), p < .05). Multivariate factor analysis indicated that impairment in the gross function influenced motor dual-task performance (B = 0.086, p = .031) and cognitive dual-task performance (B = 0.083, p = .010). Cognitive dual-task performance was affected by leg-trunk function (B = 0.063, p = .015) and age (B = −0.006, p = .009). Conclusion: The present study indicated that dual-task performance was related to motor function, balance, and fatigue, whereas gross motor function was the unique determinant of dual-task performance.